A hybrid ultrovilet detector based on polystyrene sulfate modified TiO2 nanocrystalline film. (August 2017) - Zheng, Wenji; Dong, Yanan; Yan, Xiaoming; Ding, Rui; He, Gaohong
Abstract: A hybrid polystyrene sulfate (PSS) modified TiO2 nanocrystalline (NC) composite film based ultrovilet (UV) photodetector (PD) was proposed in this study. TiO2 NC film with uniform size distribution was deposited on FTO glass by doctor blading P25 TiO2 nanoparticles. Through layer-by-layer self-assembly, PSS/TiO2 composite film was prepared and it exhibits a high responsivity of 602 AW −1, a large photo-to-dark current ratio of 193200% and a low dark current of 7 nA at only 0.1 V bias. The obtained high responsivity is almost 1–2 orders of magnitude higher than that of mostly reported TiO2 NC film based UV PDs. The reason is attributed to the injection of electrons from PSS into conduction band of TiO2 and the separation improvement of photogenerated electrons and holes by the rutile/anatase junction in the TiO2 NC film. Considering the high responsive performances and facile low-cost fabrication, the proposed PSS/TiO2 composite film based UV PD shows a bright prospect in large-area UV detection application. Highlights: A hybrid PSS/TiO2 nanocrystalline film based UV detector is proposed. The UV detector exhibits high responsivity, large on/off ratio and low dark current. The mechanism relies on the energy level match of PSS and TiO2 .